Drug survival and reasons for discontinuation of the first course of biological therapy in 301 juvenile idiopathic arthritis patients - M. Romano; I. Pontikaki; M. Gattinara; I. Ardoino; C. Donati; P. Boracchi; P.L. Meroni; V. Gerloni (PAGEPress Publications, 2014)
The objective of this study was to determine long-term effectiveness and safety of 1st biological treatment (BT) in a cohort of 301 juvenile idiopathic arthritis (JIA) patients (pts), non-responders to disease-modifying antirheumatic drugs (DMARDs), in terms of drug survival (continuation rate on therapy) and to identify the baseline predictors of treatment discontinuation. Each JIA pt enrolled in BT is prospectively assessed at the start of treatment and then every 2 months for the evaluation of safety and efficacy according to ACR-Pedi30 criteria. All clinical charts of pts who started a BT between November 1999 and July 2010 have been reviewed. Survival analysis methods suitable for competing risks were used to study time to drug discontinuation due to disease control (defined according to Wallace criteria) or failure [adverse event (AE), lack of efficacy (LaE) or loss of efficacy (LoE) according ACR-Pedi30]. A number of 301 JIA pts, non-responders or intolerant to DMARDs and treated with one or more cycles of BT, were identified. Median disease duration, from onset to the beginning of 1st BT, was 7.8 years (interquartil range 2.21-15.1). In total, there were 294 1st corses with anti-TNF agents, 5 with abatacept and 2 with anakinra. A number of 298 pts were included in the analysis for drug discontinuation (3 pts with no follow-up data after their first dose of BT were excluded). The median follow-up on treatment, before discontinuation due to every cause, was 53.7 months (range 0.45-124.45). One hundred and sixty-five pts discontinued BT: 27 due to disease control, 135 because of failure (78 AEs, 12 LaE and 45 LoE), 3 pts temporarily stopped for pregnancy. Among 135 pts who discontinued for failure, 117 switched to a 2nd BT. Among 27 pts who discontinued due to remission, 13 pts restarted on BT for relapse of disease activity (10 pts restarted with the same BT, 3 switched to a different one). Predictors of discontinuation due to AE were female gender (P=0.01) and longer disease duration (P=0.02). Predictors of discontinuation due to LaE or LoE were systemic onset and polyarthritis FR positive (vs other JIA subtypes) (P<0.05) and use of mAb-anti-TNF (vs sTNFR) (P=0.02). Predictors of discontinuation due to inactive disease were male gender and shorter disease duration (P<0.05). Although only few pts discontinued BT due to a complete and persistent disease control, the majority of them remained on BT for a long time, suggesting that in our cohort of JIA pts, affected by a severe long lasting refractory disease, BT was globally well tolerate and efficacious in controlling the disease.